ASTROLOGI SEBAGAI ILMU BANTU EPIGRAFI: Sebuah Pemikiran - Djulianto Susantio (Berkala Arkeologi, 2014)
Of the thousands of inscriptions, both stones and metals, there is only small number known as dated. Other parts are damaged, worn, or missing for various reasons. Generally, inscription contains elements of the date, month, and year in the Saka dates. With a particular method, Saka dates can be converted to AD dates. Even through the knowledge of astronomy, the element of hours can be interpreted. These four elements, namely the date, month, year, and hour are absolutely necessary in the analysis of astrology. Originally astrology is used to predict human life. However, with the development of science, it can also predict the non-human aspects, such as the important events in the history of the world. Through incisive analysis, knowledge of astronomy and astrology is very useful for epigraphy, although the time was far behind. There are several types of astrology it is commonly known, the West Astrology or Greek Astrology and East Astrology of India and China. Actually, almost all major civilizations in the world knew astrology. But among the many traditions, currently only popular Western Astrology, Chinese Astrology, Indian Astrology. Since a few years ago the West began to introduce Archaeology Metaphysics, one of them through the analysis of astrology.